Episode Berulang Malaria: Laporan Kasus: Laporan Kasus - Putri, Anindya Dwitiya; Rossiyah, Nella; Sujana, Karlina Sari; Lesmana, Suvianto Hendri (Cermin Dunia Kedokteran, 2026)
Introduction: Residents in malaria-endemic areas may experience more than 1 episode of malaria even in 1 season. Case: A 29-year-old male with fluctuating fever for 3 days accompanied by chills. The patient had just returned from Papua about 3 weeks before. The patient has worked in Papua for 1 year and has had 5 episodes of malaria: 3 falciparum malaria and 2 vivax malaria. Two months before this current complaint, the patient was taking DHP and primaquine. The patient did not take any malaria prevention drugs before leaving for Papua. Atinitial examination, the temperature was 38.6oC with leukocytosis (13,580/μL). Peripheral blood malaria examination found Plasmodium vivax parasites, stages: trophozoite and gametocyte. Patients were given DHP therapy (dihydroartemisinin 40 mg + piperaquine phosphate 320 mg) 4 times a day for 3 days and primaquine 15 mg once a day. Discussion: On the second day of treatment or the fourth day since symptom onset, the clinical condition began to improve. On the fourth day of treatment or the sixth day since symptom onset, the patient had no complaints, and vital signs and physical examination were within normal limits. The patient was discharged after continuing primaquine 15 mg for the next 11 days. Conclusion: DHP therapy (dihydroartemisinin 40 mg + piperaquine phosphate 320 mg) 4 times a day for 3 days and primaquine once at 15 mg results in a radical curative effect.